Valuing R & D Investments With A Jump-Diffusion Process - Luigi Sereno (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2006)
Traditional tools based on DCF methods fail to capture the value of R&D projects because of their dependence on future events that are uncertain at the time of the initial decision. We consider a continuous-time framework where information arrives both continuously and discontinu-ously. This is modelled by a jump-diusion process. This assumption better decribes the evolution of asset value due to the risky nature of many real investments. The main contribution of this paper is to derive a closed-form solution for the multicompound option to value sequential investment opportunities when the underlying asset may reasonably undergo the possibility of jumps in value.
Keywords: 330; Forschung; Investition; Bewertung; Stochastischer Prozess; Theorie